Review: Functions and Mechanism of Biochemical Markers in The Monitoring of Covid-19 Patients - Umaru, Isaac John; Yakubu, Kaka Garpiya; Umaru, Kerenhappuch Isaac (Darul Yasin Al Sys, 2024)
COVID-19 is an infectious disease caused by the SARSCoV-2 virus, which has given rise to a global sanitary emergency. The clinical characteristics of COVID-19 are varied and can range from an asymptomatic infection to a mild to severe pneumonia. Recent studies have shown that different laboratory parameters become altered in these patients, and as such are useful as biomarkers to assess the progression of the disease and categorize patients that may present a severe and/or fatal clinical condition. This review analyzes biochemical and immunological markers that become altered in COVID-19 patients and their impact on different organs at a hepatic, cardiac, renal and pancreatic level, as well as markers of inflammation, analyzing their implications in the evolution of the disease.